A comprehensive characterization of mitochondrial DNA mutations in glioblastoma multiforme. (June 2015) - Vidone, Michele; Clima, Rosanna; Santorsola, Mariangela; Calabrese, Claudia; Girolimetti, Giulia; Kurelac, Ivana; Amato, Laura Benedetta; Iommarini, Luisa; Trevisan, Elisa; Leone, Marco; Soffietti, Riccardo; Morra, Isabella; et al.
Abstract: Glioblastoma multiforme (GBM) is the most malignant brain cancer in adults, with a poor prognosis, whose molecular stratification still represents a challenge in pathology and clinics. On the other hand, mitochondrial DNA (mtDNA) mutations have been found in most tumors as modifiers of the bioenergetics state, albeit in GBM a characterization of the mtDNA status is lacking to date. Here, a characterization of the burden of mtDNA mutations in GBM samples was performed. First, investigation of tumor-specific vs. non tumor-specific mutations was carried out with the MToolBox bioinformatics pipeline by analyzing 45 matched tumor/blood samples, from whole genome or whole exome sequencing datasets obtained from The Cancer Genome Atlas (TCGA) consortium. Additionally, the entire mtDNA sequence was obtained in a dataset of 104 fresh-frozen GBM samples. Mitochondrial mutations with potential pathogenic interest were prioritized based on heteroplasmic fraction, nucleotide variability, and in silico prediction of pathogenicity. A preliminary biochemical analysis of the activity of mitochondrial respiratory complexes was also performed on fresh-frozen GBM samples. Although a high number of mutations was detected, we report that the large majority of them does not pass the prioritization filters. Therefore, a relatively limited burden of pathogenic mutations is indeed carried by GBM, which did not appear to determine a general impairment of the respiratory chain. This article is part of a Directed Issue entitled: Energy Metabolism Disorders and Therapies.